2012
DOI: 10.1111/1467-954x.12040
|View full text |Cite
|
Sign up to set email alerts
|

Food, Waste and Safety: Negotiating Conflicting Social Anxieties into the Practices of Domestic Provisioning

Abstract: This is the peer reviewed version of the following article: Watson, M. and Meah, A. (2012), Food, waste and safety: negotiating conflicting social anxieties into the practices of domestic provisioning. The Sociological Review, 60: 102-120, which has been published in final form at http://dx.doi.org/10.1111/1467-954X.12040. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving.eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
202
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(232 citation statements)
references
References 35 publications
10
202
0
4
Order By: Relevance
“…Evans concludes on ethnographic studies in the U.K. that consumers do not carelessly waste food [44,45]; rather, it is the socially-determined practices in food and eating and the contextual factors in which food habits are embedded that crucially impact consumer's wastage of food. Watson and Meah found that consumers seem to rarely explicitly articulate environmental concerns, but are strongly driven by an innate ethical motivation to do the "right thing" and to be thrifty, even enjoying thriftiness per se [46]. Yet, consumers also express motives that counteract food waste avoidance behaviors.…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Evans concludes on ethnographic studies in the U.K. that consumers do not carelessly waste food [44,45]; rather, it is the socially-determined practices in food and eating and the contextual factors in which food habits are embedded that crucially impact consumer's wastage of food. Watson and Meah found that consumers seem to rarely explicitly articulate environmental concerns, but are strongly driven by an innate ethical motivation to do the "right thing" and to be thrifty, even enjoying thriftiness per se [46]. Yet, consumers also express motives that counteract food waste avoidance behaviors.…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
“…The latter emerges similarly in terms of the family sacrifice connected to the usage of leftovers: it requires a certain family culture of accepting and being used to being served remains [48]. Furthermore, consumers make trade-offs between different goals, especially anxiety about the safety of food versus concern about food wastage [46,49]. Consumers thus weigh priorities on waste avoidance for the sake of the environment versus safety for oneself and immediate others.…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
“…Date labelling rules, and in particular the "best before"/"use by" dating scheme, are accused of being a source of avoidable FW, because they may be confusing for many consumers who would avoid purchasing or directly discard food approaching or passing the "best before" date, with the conviction that it could soon become or already be unsafe, or simply have lost some quality [57,85,[131][132][133][134][135]. The possibility of indicating other types of dating such as "sell-by" and "not to be used after", "display until" may add confusion [57,85,136,137] and consumer surveys have confirmed the existence of a remarkable level of misunderstanding as regards date labelling [57,[132][133][134]. The European Commission, in its action plan for the Circular Economy, announced initiatives to examine ways of improving the use of date marking and its understanding by consumers, in particular the "best before" label [8].…”
Section: Fw Drivers Related To the Agricultural Policy And To Food Qumentioning
confidence: 99%
“…Some authors have detected the presence of a geographical differentiation in the individual behaviours towards FW among the EU countries, which is likely to depend on contextual factors, for example: the income per-capita, which seems positively correlated to household FW generation, and the citizens' perception towards sustainability issues, indirectly measured through various indicators [15]. According to several surveys, consumers in general deem that modern "busy" lifestyles make it much more difficult to perform good practices correctly that facilitate FW avoidance [16,25,[153][154][155][156]: in this sense, sociological analyses defined FW as "the fallout of the organization of everyday life" [136], and "a consequence of households enacting ordinary domestic practices and negotiating the contingencies of everyday life" [157]. Authors have also found gender-based diversities in FW generating behaviours, with women that seem to waste more than men in households [14,30,55,153,158,159], especially in single-person households and in meal consumption out of home because of excessive portion size [23].…”
Section: Fw Drivers Related To Wide Social Dynamics That Are Not Readmentioning
confidence: 99%
“…Finally, consumer research illustrates how diet-related decisions raise a host of ethical challenges and complex trade-offs which may seem insuperable in principle but which are 'negotiated into practice' by consumers on a daily basis (Watson and Meah 2013). So, for example, consumer preference for organic food (on health or sustainability grounds) may be traded off against a desire for local food (produced via intensive farming methods but with fewer 'food miles') -or the immediate demand to feed one's family in the most economical way may trump more abstract ethical commitments to 'distant strangers' in far-off producer countries ).…”
mentioning
confidence: 99%